EVALUATION OF SERUM URIC ACID AND LIPID PROFILE IN GESTATIONAL HYPERTENSION. - DR. P.JOSEPHINE LATHA; DR. S.GANESAN (International Journal of Pharma and Bio Sciences, 2013)
Gestational hypertension (GH) is one of the causes for increased maternal morbidity and mortality and leads to 15% of preterm births. Dyslipidaemia and hyperuricemia are suggested to have pathophysiological role. 100 women with GH and 100 normotensive pregnant women were included in the study. Serum Glucose, lipid profile and uric acid were estimated by standard enzymatic methods. In our study the total cholesterol, triglycerides, LDL-C, VLDL-C and uric acid were significantly elevated and HDL-C was significantly decreased in GH group compared to control (p< 0.0001). Uric acid showed significant positive correlation with systolic blood pressure, TGL, and TGL/HDL (r = 0.287, p < 0.01; r = 0.551, p < 0.001; r = 0.429, p < 0.001 respectively) and negative correlation with HDL/VLDL (r = -0.415, p < 0.001).TGL showed significant positive correlation with diastolic blood pressure (r = 313, p = 0.001); uric acid(r = 0.551, p < 0.001), TGL/HDL (r = 0.762, p < 0.001) and negative correlation with HDL/VLDL (r = -0.701, p < 0.001). Lipid profile and serum uric acid measurements in the early 2nd trimester can be suggested as cost-effective markers in the prevention of the complications of GH.